SURGICAL TREATMENT OF FOOT DROP AFTER PERONEAL NERVE INJURY - Nikolić, Živan; Rasulić, Lukas (Medicinski podmladak, 2024)
Foot drop is a common clinical condition presented as an inability to lift the forefoot, characterized by the loss of ankle dorsiflexion from the tibialis anterior and loss of foot eversion from the peroneus longus and brevis muscles, followed by sensory loss or numbness of the foot dorsum. Causes of a foot drop can happen at any level of the nerve path. By their nature, lesions can be divided into compressive disorders, traumatic injuries, and neurologic disorders. Peroneal palsy, due to compression, is the most common peripheral cause. Treatment and diagnosis of foot drop still need to be better standardized, given that foot drop is still considered a clinical sign in other conditions. Regarding the multidisciplinary nature of foot drop, it can be challenging to determine the cause. Surgical and conservative treatments have their own respective places. Conservative procedures used for foot drop treatment include physical therapy, functional electrical stimulation, orthosis and braces, assistive devices, and gait training. Depending on a different etiological factor that causes foot drop, a few different surgical techniques are available for successful surgical treatment. Peroneal nerve release is considered a low-risk procedure with excellent results, such as pain relief and return of function. If the nerve continuity is not preserved nerve repair with epineural stitches under magnification is performed. Another surgical approach proven successful in literature is nerve transfer. Sural nerve is usually donor graft. For tendon transfer tibialis posterior muscle is usually chosen. As it is inserted at the dorsum of the foot, it helps with dorsiflexion. After all surgical procedures, it is advised for patients to start with early mobilization and postoperative physical therapy. Better treatment standardization of foot drop is still needed. However, surgical procedures show high success rates, better results, and faster recovery if performed within the first months of injury.